2006
DOI: 10.4310/cag.2006.v14.n3.a6
|View full text |Cite
|
Sign up to set email alerts
|

Toroidal Dehn fillings on large hyperbolic 3-manifolds

Abstract: We show that if a hyperbolic 3-manifold M with a single torus boundary admits two Dehn fillings at distance 5, each of which contains an essential torus, then M is a rational homology solid torus, which is not large in the sense of Wu. Moreover, one of the surgered manifolds contains an essential torus which meets the core of the attached solid torus minimally in at most two points. This completes the determination of best possible upper bounds for the distance between two exceptional Dehn fillings yielding es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Others have made similar observations. Notably, Teragaito [29] conjectured that integral exceptional surgeries occur as a sequence of consecutive integers. Dunfield [10] showed that, for small knots, if surgery along slope r yields a manifold with cyclic fundamental group, then there is a non-integral boundary slope in the interval (r − 1, r + 1).…”
Section: Introductionmentioning
confidence: 99%
“…Others have made similar observations. Notably, Teragaito [29] conjectured that integral exceptional surgeries occur as a sequence of consecutive integers. Dunfield [10] showed that, for small knots, if surgery along slope r yields a manifold with cyclic fundamental group, then there is a non-integral boundary slope in the interval (r − 1, r + 1).…”
Section: Introductionmentioning
confidence: 99%